50th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2012
DOI: 10.2514/6.2012-393
|View full text |Cite
|
Sign up to set email alerts
|

From Spreadsheets to Simulation-Based Aircraft Conceptual Design

Abstract: An automated, simulation-based aircraft design process allows for the prediction of unanticipated problems early in the design stage, leading to reduced turn-around time and development cost. Having reliable, and affordable (fast) design tools is crucial to achieving this level of automation in the design process. An example of this is illustrated for a jet trainer aircraft using two aircraft design codes: Jet Designer and CEASIOM which includes Digital DATCOM, a Vortex lattice method, and an Euler flow solver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…For Short Period oscillations, according to the CS-23 criteria, the characteristics were very significant. With respect to Figure 17 which shows the short period undamped natural frequency against different acceleration sensitivity values, the results met the Level 1 requirements according to MIL requirements [70]. Furthermore, Figure 18 presents the damping ratio for the short mode, which nicely satisfies Level 1 of handling quality according to the CS-23 criteria [34].…”
Section: Resultsmentioning
confidence: 67%
“…For Short Period oscillations, according to the CS-23 criteria, the characteristics were very significant. With respect to Figure 17 which shows the short period undamped natural frequency against different acceleration sensitivity values, the results met the Level 1 requirements according to MIL requirements [70]. Furthermore, Figure 18 presents the damping ratio for the short mode, which nicely satisfies Level 1 of handling quality according to the CS-23 criteria [34].…”
Section: Resultsmentioning
confidence: 67%
“…Kostic´et al 11 compared results of a VLM-based method with the DD for a light aircraft in the linear range, and indicated that the lift and pitching moment coefficients of two methods agree well with each other in the presence of elevator and flap deflections. For more information about the verification and validation of semi-empirical methods, one can refer to Smith, 12 Da Ronch et al, 13 Siddiqui et al, 14 Ghoreyshi and Cummings, 15 Gabor et al 16 and Ul Haque et al 17…”
Section: Literature Reviewmentioning
confidence: 99%
“…6 The absence of the fuselage has a considerable impact on the stability and aerodynamics of the geometry as a fuselage typically shifts the aerodynamic centre aft, thus a Wing-Tail geometry is likely to be longitudinally stiffer than a Wing-Body-Tail configuration. 13 In the context of a wing-tail only configuration, this makes the choice of location to be studied challenging as computationally modelling of such comprehensive datasets 9 would be exhaustive. Furthermore, results involving the midspan (along aircraft symmetry plane) are likely to be interfered by a fuselage.…”
Section: Introductionmentioning
confidence: 99%